AMONG LANGUAGES-CULTURES: PORTUGUESE LANGUAGE ∞ INDIGENOUS LANGUAGE (PERcursos Linguísticos, 2022)
ABSTRACT: This article aims to analyze representations of languages ​​(Portuguese and Indigenous) that emerge in the essays of indigenous people participating in the Access and Permanence Program for Indigenous Peoples (PIN) of the Federal University of Fronteira Sul (UFFS). With this, some discursive sequences of essays elaborated in PIN-UFFS (2015 and 2018 selection) were selected, which, through discursive regularities, allowed us to compose our interpretive gesture. We use a discursive-deconstructivist perspective, with authors who dedicate their efforts to questions of language and identity such as Pêcheux (2010), Coracini (2007) Lacan (2005) and Derrida (2001). When observing the arrival of indigenous students to UFFS, it led us to question how the language and, consequently, the identity of these people are affected when they need to adapt themselves to the place historically belonging to the non-indigenous: the university. We understand this can lead to the erasure of these Indigenous languages. The results point to a rupture in relation to the native language of the indigenous and a conflict in being among languages-cultures (Portuguese language ∞ indigenous).